A dorsal visual route necessary for global form perception: evidence from neuropsychological fMRI. - Lestou, V; Lam, J; Humphreys, K; Kourtzi, Z; Humphreys, G (2014)
Hierarchical models of visual processing assume that global pattern recognition is contingent on the progressive integration of local elements across larger spatial regions, operating from early through intermediate to higher-level cortical regions. Here, we present results from neuropsychological fMRI that refute such models. We report two patients, one with lesions to intermediate ventral regions and the other with damage around the intraparietal sulcus (IPS). The patient with ventral damage showed normal behavioral and BOLD responses to global Glass patterns. The patient with IPS damage was impaired in discriminating global patterns and showed a lack of significant responses to these patterns in intermediate visual regions spared by the lesion. However, this patient did show BOLD activity to translational patterns, where local element relations are important. These results suggest that activation of intermediate ventral regions is not necessary to code global patterns; instead global patterns are coded in a heterarchical fashion. High-level regions of dorsal cortex are necessary to generate global pattern coding in intermediate ventral regions; in contrast, local integration processes are not sufficient.